Analysys and Implementation IEEE 802.1Q to Improve Network Security - Bahry, Muhammad Syaeful; Sugiantoro, Bambang (IJID (International Journal on Informatics for Development), 2017)
The development of technology today is very fast one only with the existence of the use of the computer network. This can be seen in the increasing number of organizations or companies that use the computer network to facilitate the flow of information within the organization or the company. But with the abundance of the use of network technology is only advancing network progressed only, but not maximize resource so that sometimes allows for the problem or traffic network. For that can be needed by network development solution made VLAN topology using NDLC method (Network Development Life Cycle). Vlans are able to improve the capabilities of the network and can reduce the amount of data that is sent to a destination that does not need to be so that the traffic in the network will be reduced by itself. In addition there is another reason why requires a VLAN is to reduce the possibility of the misuse of access rights. It can use the Mode Access. With the Mode will divide each Host into the VLAN each. With the existence of a VLAN shows can increase network ability as much as 13.4 %. With the data shows that a VLAN successful and able to make the network more efficient. In the VLAN network security aspect is able to optimize network security with the existence of access mode, so that the new host are not capable of entering it into the existing network topology.